Genetic parameter estimates for milk yield and lactation length in Buffalo - García, Yenny; Fraga, Luis M.; Tonhati, Humberto [UNESP]; Abreu, Daniel [UNESP]; Aspilcueta, Raúl [UNESP]; Hernández, Arelis; Padrón, Eulogio; Guzmán, Gladys; Mora, Marta; Quiñonez, Dayron (My University, 2013)
The objective of this study was to estimate genetic parameters for milk yield at 244 days and lactation length in graded buffalo cows at the El Cangre Cattle Genetic Enterprise. Data were gathered from 2575 lactations, 1377 buffalo cows, 37 milking units and between 2002-2009 calving years. It was employed the Restricted Maximum Likelihood method (REML) for estimating (co)variance components with multi trait model. Average of milk yield at 244 days and lactation length were 864 kg and 240 days, respectively. Heritability was 0.15 for milk yield and 0.13 for lactation length. Genetic correlation between these traits was 0.63. It was concluded that it is necessary to intensify selection and to increase control of the information of the genetic herds to obtain high precision in the estimates and therefore, obtain bigger genetic progress in of this species in our country.
Keywords: Buffalo; Genetic parameters; Milk yield